Entre algoritmos e autoimagem: a construção identitária no ambiente das plataformas de redes sociais digitais - Coelho, Pietro Giuliboni Nemr (2024)
The environment of digital social media platforms allows users to contact friends and family, participate in discussions, produce and share original content in real-time. Through symbolic consumption, users select objects, symbols, and elements that will compose their content, to express their tastes, opinions, and values to other individuals, building their identities in this environment. In the functioning of the platforms, we highlight the presence and performance of algorithms that, through the collection and analysis of user data, provided during their digital activities, act to organize these spaces, establishing rules, and standards of conduct, and promoting actions that seek to improve user experience, such as new services, content recommendations, among others. From this scenario, the research developed discusses how this performance of algorithms within digital social media platforms, indicating posting patterns, forms of behavior, and themes to users, can be related to identity construction processes, as it can encourage them to adopt certain pre-established posting and browsing actions, in addition to encouraging frequent use of the platforms, establishing a scenario of alienation, replication and manipulation of behavior. Supported by Bruns, Castells, Couldry, Douglas, Kellner, Primo, Van Djick, Tondato, and Zuboff among others, we reflect on the scenario of digital platforms, as well as the processes of capturing and using data, the functioning of algorithms, and how these factors are related to consumption habits and the process of identity construction within the environment of PRSDs in the context of postmodern society. We conducted interviews with users of the Instagram and TikTok applications, with whom we established a discussion about platform usage habits, perceptions regarding the construction of identities, and impressions about the performance of algorithms in their browsing and posting activities. Even though they are technologies whose functioning is not fully disclosed, how they operate is perceived by users as providing a better experience of browsing and using the platforms, as it optimizes the production and performance of their content, which is reflected in the construction identity. However, it can establish a scenario of standardization and replication of behaviors.